The autograph man, by Zadie Smith: the long way to heal trauma - Wood, Jorge Berástegui (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Zadie Smith’s second novel, The Autograph Man (2002), was severely reviewed by several critics who expected another ‘multicultural novel’ after her first literary success, White Teeth (2000). This paper aims to reflect on the importance of this second novel and to highlight the relevance of trauma in contemporary culture, which negates and is fascinated by this phenomenon. Through an analysis of the main character of the novel, this work reflects on how human beings try to escape the psychological effects of traumatic events, instead of facing the painful feelings they provoke and the changes they produce on the human psyche.